Which mechanisms explain motivation the of primary health workers? Insights from the realist evaluation of a maternal and child health programme in Nigeria. Issue 8 (25th August 2020) - Ebenso, Bassey; Mbachu, Chinyere; Etiaba, Enyi; Huss, Reinhard; Manzano, Ana; Onwujekwe, Obinna; Uzochukwu, Benjamin; Ezumah, Nkoli; Ensor, Timothy; Hicks, Joseph Paul; Mirzoev, Tolib
Abstract : Introduction: Well-trained, adequately skilled and motivated primary healthcare (PHC) workers are essential for attaining universal health coverage (UHC). While there is abundant literature on the drivers of workforce motivation, published knowledge on the mechanisms of motivation within different contexts is limited, particularly in resource-limited countries. This paper contributes to health workforce literature by reporting on how motivation works among PHC workers in a maternal and child health (MCH) programme in Nigeria. Methods: We adopted a realist evaluation design combining document review with 56 in-depth interviews of PHC workers, facility managers and policy-makers to assess the impact of the MCH programme in Anambra State, Nigeria. A realist process of theory development, testing and consolidation was used to understand how and under what circumstances the MCH programme impacted on workers' motivation and which mechanisms explain how motivation works. We drew on Herzberg's two-factor and Adam's equity theories to unpack how context shapes worker motivation. Results: A complex and dynamic interaction between the MCH programme and organisational and wider contexts triggered five mechanisms which explain PHC worker motivation: (1) feeling supported, (2) feeling comfortable with work environment, (3) feeling valued, (4) morale and confidence to perform tasks and (5) companionship. Some mechanisms were mutually reinforcing while others operated in parallel. Other conditions that enabled worker motivation were organisational values of fairness, recognition of workers' contributions and culture of task-sharing and teamwork. Conclusions: Policy designs and management strategies for improving workforce performance, particularly in resource-constrained settings should create working environments that foster feelings of being valued and supported while enabling workers to apply their knowledge and skills to improve healthcare delivery and promote UHC. Future research can test the explanatory framework generated by this study and explore differences in motivational mechanisms among different cadres of PHC workers to inform cadre-related motivational interventions.